Are clam-seagrass interactions affected by heatwaves during emersion?. (April 2023) - Román, Marta; Gilbert, Franck; Viejo, Rosa M.; Román, Salvador; Troncoso, Jesús S.; Vázquez, Elsa; Olabarria, Celia
Abstract: The increased frequency of heatwaves expected in the context of global warming will affect socio-ecological systems such as shellfish beds at intertidal seagrass meadows. A mesocosm experiment was performed to assess the effects of a simulated atmospheric heatwave during low tide on the bioturbation indicators and growth of the commercial juvenile native Ruditapes decussatus and the introduced clam R. philippinarum, and on their interactions with the seagrass Zostera noltei. Under the heatwave, heat dissipation at 5 cm depth was significantly greater in the sediments below Z. noltei than below bare sand, the photosynthetic efficiency (Fv /Fm ) of Z. noltei decreased and the clams tended to grow less. Furthermore, after the heatwave clams below bare sand tended to burrow deeper than those below Z. noltei, indicating that seagrass provided a refuge for clams. Ruditapes philippinarum grew less, and did not burrow as deeply as R. decussatus, which may imply greater vulnerability to desiccation and heat at low tide. The particle displacement coefficient (PDC) of R. philippinarum indicated lower bioturbation values in Z. noltei than in bare sand and was a suitable bioturbation indicator for juvenile Ruditapes spp. clams. In Z. noltei coexisting with R. philippinarum, the Fv /Fm values were higher than without clams after a recovery period, which may be linked to the assimilation of phosphate excreted by the clams and suggests a facilitative interaction. No such interaction was observed with R. deccusatus, probably because of its deeper burrowing depth. The findings suggest reciprocal facilitative interactions between R. philippinarum and Z. noltei and the potential contribution of Z. noltei to the sustainability of clams under global warming scenarios, which may support management actions aimed at enhancing the coexistence between shellfishing activities and seagrass conservation. Graphical abstract: Image 1 Highlights: The effect of a heatwave during low tide on clam - seagrass interactions was tested. Clam bioturbation and growth, seagrass photosynthetic efficiency (Fv /Fm ) and pore water nutrients were measured. Heat dissipation in the sediment was greater below Z. noltei than below bare sand. The particle displacement coefficient was a good bioturbation indicator for venerids Fv /Fm in Z. noltei and PO4 3− in pore water increased with R. philippinarum .